Examining Compulsive Online Shopping Behavior, Posttraumatic Cognitions, and Death Anxiety in Young Adults - Traş, Zeliha; Yakıcı, Hikmet Beyza (Addicta: The Turkish Journal on Addictions, 2025)
This study aims to examine the relationships between compulsive online shopping behavior (COSB), posttraumatic cognitions, and death anxiety in young adults. In this study, the relational research model, one of the quantitative research methods, was used. The study group was determined by the criterion sampling method. The study group consisted of 467 young adults (x̄ = 28.09), 372 females, and 95 males. According to the results, compulsive online shopping behavior differs significantly in favor of female young adults according to the gender variable and in favor of single young adults according to the marital status variable. compulsive online shopping behavior shows a significant difference in favor of individuals with 5–6 hours of daily Internet use on weekdays and weekends according to the duration of internet use on week-days and weekends. Results of correlation analysis show a significant positive relationship between young adults’ COSB scores, posttraumatic cognition scores, and death anxiety scores. According to the hierarchical regression analysis, death anxiety and posttraumatic cognition scores significantly predicted COSB scores. As a result of the mediation analysis, death anxiety plays a mediating role in the relationship between posttraumatic cognitions and COSB. The findings suggest that psychological factors such as posttraumatic cognitions and death anxiety play an important role in shaping compulsive online shopping behavior.